2006
DOI: 10.1016/j.trstmh.2005.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporium apiospermum mycetoma with bone involvement successfully treated with voriconazole

Abstract: Treatment of Scedosporium apiospermum mycetoma usually requires limb amputation. A 49-year-old woman, from Ivory Coast, was diagnosed with Madura foot in 1995. She failed to respond to several treatments including itraconazole, fluconazole and co-trimoxazole, and refused limb amputation. In December 2002 she was admitted to hospital in France with a painful, swollen right leg and foot. She had no fever and C-reactive protein was 120 mg/l. Magnetic resonance imaging (MRI) confirmed the destruction of tarsus bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…This could be explained by the fact that we have tested a greater number of isolates than previous studies. The poor activity of ITC agrees with the failure of this drug to resolve some clinical cases (9,13). The treatment of Pseudallescheria infections is often challenging and complex.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…This could be explained by the fact that we have tested a greater number of isolates than previous studies. The poor activity of ITC agrees with the failure of this drug to resolve some clinical cases (9,13). The treatment of Pseudallescheria infections is often challenging and complex.…”
mentioning
confidence: 82%
“…However, the new triazoles, such as voriconazole (VRC), ravuconazole (RVC), and posaconazole (PSC), have shown some in vitro activities against this fungus (5). VRC has also shown efficacy both in animal models (3,4) and in the clinical setting (1,13). However, not all the strains of P. boydii tested responded equally to VRC.…”
mentioning
confidence: 99%
“…Voriconazole may show fungicidal activity against S. apiospermum and is efficacious in both mouse and guinea pig models of scedosporiosis (4,5,10). In humans, numerous case reports have detailed its clinical effectiveness against Scedosporium infections, including those involving the central nervous system (CNS) and bone (6,12,13,14,20,22,23,34,35,39,40,47). Most describe the use of voriconazole as the sole antifungal agent, sometimes combined with surgery.…”
mentioning
confidence: 99%
“…Imidazole has been demonstrated to be effective for S. apiospermum infection in vitro, although for invasive and disseminated S. apiospermum infection, imidazole is often ineffective (17). In addition, although some case reports have demonstrated successful outcomes with itraconazole, the overall effects are poor (18,19). Troke et al (20) reported that, in 107 cases of Scedosporium infection in which the principal infection sites were the lungs/sinuses (24%), central nervous system (CNS) (20%) and bone (18%), 21% of the patients had disseminated infection, and successful therapeutic responses were observed in 57% of the patients treated with voriconazole.…”
Section: A B C Dmentioning
confidence: 99%